2018
DOI: 10.1108/er-01-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Does e-HRM improve labour productivity? A study of commercial bank workplaces in Pakistan

Abstract: Purpose Drawing on data from a unique, large-scale survey, the purpose of this paper is to examine the links between e-HRM and perceived labour productivity both directly and through the mediating role of HR service quality amongst commercial-bank workplaces in Pakistan, many of which have introduced e-HRM. Design/methodology/approach The authors use partial least squares structural equation modelling to examine the direct links between e-HRM and productivity as well as the mediated links between e-HRM, perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 74 publications
2
52
0
2
Order By: Relevance
“…Thus, it shows that the performance of an organization relates to the productivity of the workforce within the organization itself. This was confirmed that stated greater use of EHRM practices directly leads to an improvement in labor productivity [7].…”
Section: Background Of Studysupporting
confidence: 71%
“…Thus, it shows that the performance of an organization relates to the productivity of the workforce within the organization itself. This was confirmed that stated greater use of EHRM practices directly leads to an improvement in labor productivity [7].…”
Section: Background Of Studysupporting
confidence: 71%
“…Due to a lack of universal e-HRM practices, the use of e-HRM practices varies from country to country and industry to industry (Iqbal, Ahmad, Allen, & Raziq, 2018;Obeidat, 2016). Bondarouk et al (2016) and Iqbal et al (2018) argue that there is limited empirical evidence on the e-HRM value creation proposition from the developing country context. Research suggests that country specific empirical evidence is essential to conclude the e-HRM value creation debate (Ahmad & Allen, 2015;Panayotopoulou, Galanaki, & Papalexandris, 2010).…”
Section: Context Of the Studymentioning
confidence: 99%
“…Therefore, we select banks where e-HRM has been used for more than one year. Iqbal et al (2018) suggest that line managers are central to interpreting e-HRM value creation. Purcell and Hutchinson (2007) highlight the importance of the perceptions of line managers to explaining the HRM-performance causal chain.…”
Section: Datamentioning
confidence: 99%
“…The increasing demand for information technologies (IT) within the field of human resource management (HRM) changes the way organizations handle human resource (HR) [1,2]. Organizations have early recognized that HRM benefits from the use of new IT [3] as it increases labor productivity [4] and shifts the organizational role of HRM to a more strategic one [3,[5][6][7]. Thus, organizations make huge efforts to push electronic HRM (e-HRM).…”
Section: Introductionmentioning
confidence: 99%